Differential dendritic targeting of AMPA receptor subunit mRNAs in adult rat hippocampal principal neurons and interneurons. Issue 9 (18th April 2013) - Cox, David J.; Racca, Claudia
Abstract In hippocampal neurons, AMPA receptors (AMPARs) mediate fast excitatory postsynaptic responses at glutamatergic synapses, and are involved in various forms of synaptic plasticity. Dendritic local protein synthesis of selected AMPAR subunit mRNAs is considered an additional mechanism to independently and rapidly control the strength of individual synapses. We have used fluorescent in situ hybridization and immunocytochemistry to analyze the localization of AMPAR subunit (GluA1–4) mRNAs and their relationship with the translation machinery in principal cells and interneurons of the adult rat hippocampus. The mRNAs encoding all four AMPAR subunits were detected in the somata and dendrites of CA3 and CA1 pyramidal cells and those of six classes of CA1 γ‐aminobutyric acid (GABA)ergic interneurons. GluA1–4 subunit mRNAs were highly localized to the apical dendrites of pyramidal cells, whereas in interneurons they were present in multiple dendrites. In contrast, in the dentate gyrus, GluA1–4 subunit mRNAs were virtually restricted to the somata and were absent from the dendrites of granule cells. These different regional and cell type‐specific labeling patterns also correlated with the localization of markers for components of the protein synthesis machinery. Our results support the local translation of GluA1–4 mRNAs in dendrites of hippocampal pyramidal cells and CA1 interneurons but not in granule cells of the dentate gyrus. Furthermore, the regional and cell type‐specific differences we observed suggest that each cell type uses distinct ways of regulating the local translation of AMPAR subunits. J. Comp. Neurol. 521:1954–2007, 2013. © 2012 Wiley Periodicals, Inc.